The vibration of a beam embedded with piezoelectric inclusions - Deng, Chao Dan (2008)
Active vibration control using smart materials has attracted more and more attentions in recent years. In the present project, the dynamic response of a beam embedded with arrays of piezoelectric actuators/sensors is investigated. The analytical model is based on Hamilton's Variational Principle [Grant, 1986] and Eshelby's Equivalent Inclusion method [Mura, 1982] following Alghamdi A. [Alghamdi and Dasgupta, 1993-1995]. The previously neglected energy in the vicinity of the embedded inclusions is included and compared with published experimental results by Alghamdi. The close-to-surface effect of the embedded inclusions is considered. The results show the capability of using piezoelectric devices to control the vibrational behaviour of a structure.